Validation of Symptoms Related to Excessive Daytime Sleepiness - Rinaldi, Rita; Vignatelli, Luca; D’Alessandro, Roberto; Bassein, Leona; Sforza, Emiliana; Plazzi, Giuseppe; Provini, Federica; Lugaresi, Elio (Neuroepidemiology, 2001)
The aim of this study was to validate some recurring definitions of excessive daytime sleepiness (EDS) obtained from descriptive epidemiological studies. We devised questions concerning concepts such as ‘tiredness’, ‘resistible sleepiness’, ‘irresistible sleepiness’ and ‘sudden sleep attacks’. The validation was done by comparing the answers with the results of the Multiple Sleep Latency Test (MSLT), considered the gold standard, or criterion measure, for the diagnosis of EDS. The sample study comprised 73 subjects, 57 outpatients referred to our Sleep Center complaining of daytime sleepiness, snoring or sleep apnea and 16 inpatients admitted to our Neurological Institute for causes other than sleep disorders. A moderate correlation (p = –0.38, 95% confidence interval –0.57 to –0.19) was found between ‘irresistible sleepiness’ and mean sleep latency (MSL). The best combinations of sensitivity and specificity in identifying EDS, for 5- and 8-min MSL cutoffs, were observed for the questions concerning ‘sudden sleep attacks’ and ‘irresistible sleepiness’ (areas under the receiver-operating characteristic curves = 66 and 67%, respectively). The subitems exploring the frequency and situations of occurrence of these symptoms improved the validity in identifying EDS. The items regarding ‘tiredness’ and ‘resistible sleepiness’ were not related to the results of the MSLT. In subgroup analysis, irresistible sleepiness failed to identify pathologic MSLT in sleep-disordered breathing subjects. According to previous observations, we suggest that the concept of sleepiness includes various domains heterogeneously related with MSL and that questionnaires must be tailored to the different populations studied.